PENERAPAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) UNTUK MENGANALISIS KUALITAS APLIKASI TOKOPEDIA BERDASARKAN KEPUASAN PELANGGAN - Tita Moladia; Titin Kristiana (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2023)
Tokopedia is an e-commerce that has 158 million visitors per month and is one of the most visited e-commerce. As an e-commerce site with the most visitors, Tokopedia should provide good service so that after making a transaction customers feel satisfied and in the future will use the same application to shop. Through the quality of products and services offered, the quality of services has a strong relationship with the company's profits. Customer satisfaction depends on the standards and quality of the company. Along with the rapid development of e-commerce, companies are competing to create new features for the convenience of customers when shopping and to be able to excel in competing with other e-commerce. Therefore, the use of the Importance Performance Analysis (IPA) method is expected to be a method to analyze customer satisfaction in order to improve the quality of products and services on the Tokopedia application. From the use of the IPA method, it can be seen that the Tokopedia application obtained a conformity level value of 98.7% where the value was <100% and from the gap analysis the result was negative, namely -0.06 where the value was considered not in accordance with user expectations so that based on the values of the attributes that are the assessment criteria, it can be considered to improve its performance.